Formulation and Numerical Solution for Fractional Order Time Optimal Control Problem Using Pontryagin's Minimum Principle. Issue 1 (July 2017) - Tabatabaei, S. Sepehr; Yazdanpanah, Mohammad Javad; Tavazoei, Mohammad Saleh
Abstract: The main purpose of this paper is to use variational calculus and Pontryagin's minimum principle to propose a solution scheme for time optimal control problem stated on the fractional systems defined in the sense of Caputo. After deriving the necessary optimality conditions, a novel numerical solution is used to solve the problem. Afterwards, a simple case study shows the effectiveness of the proposed method.